Effect of Cold Rolling and Annealing Temperature to the Characteristics of α + β’ Phases in Cu-29.5Zn-2.5Al Alloy Produced by Gravity Casting (Journal of Mining and Metallurgy, Section B: Metallurgy, 2020)
Al-brass alloys (Cu-29.5Zn-2.5Al wt. %) were produced by gravity casting and homogenized at 800 oC for 2 h, resulting in binary phase morphology identified as cubic α and martensitic β’ phases through X-ray Diffraction (XRD) analysis. Samples were then subsequently cold rolled and annealed at 150, 300, 400, and 600 oC for 30 minute. Visible traces of slip, cross-slip, twinning, and shear bands were observed in microstructure images of the samples after each progressive deformation stages. Higher thickness reduction resulted in simultaneous strain hardening of present phases. Low temperature annealing slightly increased microhardness, of both α and β’, allegedly due to the formation of Cottrell atmosphere. It was inferred from the results of SEM-EDS analysis that solute segregation was not found in annealed samples.  Annealing at higher temperature resulted in conventional softening through stress recovery mechanism. Recrystallized β’ phase grains in equiaxed shape were visible after annealing at 600 oC.